School entry, afternoon care, and mothers' labour supply - Ludovica Gambaro; Jan Marcus; Frauke Peter (Empirical Economics, 2019)
The availability of childcare is a crucial factor for mothers' labour force participation. While most of the literature examines childcare for preschool children, we specifically focus on primary school-aged children, estimating the effect of formal afternoon care on maternal labour supply. To do so, we use a novel matching technique, entropy balancing, and draw on the rich and longitudinal data of the German Socio-Economic Panel (SOEP). We show that children's afternoon care increases mothers' employment rates and their working hours. To confirm the robustness of our results, we conduct a series of sensitivity analyses and apply a newly proposed method to assess possible bias from omitted variables. Our findings highlight how childcare availability shapes maternal employment patterns well after school entry.
Keywords: J13; J63; J65; 330; Afternoon care; Maternal labour supply; All-day schools; Entropy balancing